2005
DOI: 10.1007/s11099-005-0082-2
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective effects of high level expression of C<sub>4</sub> phosphoenolpyruvate carboxylase in transgenic rice during photoinhibition

Abstract: With untransformed rice cv. Kitaake as control, the characteristics of carbon assimilation and photoprotection of a transgenic rice line over-expressing maize phosphoenolpyruvate carboxylase (PEPC) were investigated. The PEPC activity in untransformed rice was low, but the activity was stimulated under high irradiance or photoinhibitory condition. PEPC in untransformed rice contributed by about 5-10 % to photosynthesis, as shown by the application of the specific inhibitor 3,3-dichloro-2-(dihydroxyphosphinoylm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 29 publications
(19 reference statements)
0
14
0
2
Order By: Relevance
“…Moreover, the photosynthetic characteristics and the tolerance to photoinhibition and photo-oxidation in JAAS45 were similar to those of the male parent. On the other hand, we also found that JAAS45, similar to PEPC transgenic rice, possesses a limiting C 4 -like cycle with primitive CO 2 concentrating mechanism (Jiao et al 2003). All this suggests that the PEPC transgenic rice can transfer over-expression of PHOTOSYNTHETIC CHARACTERISTICS OF HYBRID RICE WITH PHOSPHOENOLPYRUVATE CARBOXYLASE GENE PEPC activity and the C 4 photosynthetic characteristics into conventional rice.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…Moreover, the photosynthetic characteristics and the tolerance to photoinhibition and photo-oxidation in JAAS45 were similar to those of the male parent. On the other hand, we also found that JAAS45, similar to PEPC transgenic rice, possesses a limiting C 4 -like cycle with primitive CO 2 concentrating mechanism (Jiao et al 2003). All this suggests that the PEPC transgenic rice can transfer over-expression of PHOTOSYNTHETIC CHARACTERISTICS OF HYBRID RICE WITH PHOSPHOENOLPYRUVATE CARBOXYLASE GENE PEPC activity and the C 4 photosynthetic characteristics into conventional rice.…”
mentioning
confidence: 51%
“…Till now, only a few systematic studies on photosynthetic characteristics of transgenic rice with maize phosphoenolpyruvate carboxylase (PEPC) have been carried out. They show that such transgenic rice expresses high PEPC activity similar to that in maize (Chi et al 2001) and has better photosynthetic capacity with enhanced tolerance to photo-oxidation (Jiao et al , 2005, as compared with untransformed rice cv. Kitaake.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the properties of PEPCase in C 4 plants are modified compared to the C 3 form, such that the mutants lacking it, are unable to assimilate atmospheric CO 2 (Dever et al 1995, Cholett et al 1996. Since PEPCase has a high affinity for CO 2 , overexpression of the enzyme is considered to be a promising approach to enhance the efficiency of carbon fixation (Miyao and Fukayama 2003, Jiao et al 2005, El-Sharkawy 2009.…”
Section: Overexpression Of C 4 Enzymesmentioning
confidence: 99%
“…Similarly, overexpression of PEPCase and PPDK in rice improved its photosynthetic capacity with enhanced tolerance to photo-oxidation and produced 22-24% more grains (Jiao et al 2002). Transgenic rice overexpressing PEPCase was shown to be more tolerant to photoinhibition that could improve protection from photooxidation (Jiao et al 2005, Zhang et al 2009). …”
Section: Overexpression Of C 4 Enzymesmentioning
confidence: 99%